A positive electrode active material for an all-solid-state battery, a composite positive electrode material, and a preparation method and applications thereof

CN123017948APending Publication Date: 2026-10-30PEKING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611430409.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

解决了现有技术中硫/硫化锂在充放电过程中存在明显体积变化导致破坏正极内部固-固接触进而阻碍电子和离子传输的问题

Benefits of technology

(1)本发明提供的用于全固态电池的正极活性材料,采用通式为S10-x-Ix的硫碘复合物,在充放电过程中,所述硫碘复合物中预引入的I2相能够以I2/I-氧化还原电对的形式发生快速、可逆的氧化还原反应,从而介导加快复合正极材料中金属硫化物与S之间的固-固转化。另外,当全固态电池的正极使用硫化物固态电解质时,I2相与硫化物固态电解质接触能原位发生氧化还原反应形成I2/I-纳米网络结构,其作为I2/I-固-固氧化还原介质,能在充放电过程中发生可逆氧化还原反应,进一步加强化学介导金属硫化物/S的固-固转化的作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017948A_ABST
    Figure CN123017948A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of all-solid-state batteries, in particular to a positive electrode active material for an all-solid-state battery, a composite positive electrode material and a preparation method and application thereof. The positive electrode active material comprises a sulfur-iodine composite with a general formula of S 10‑x ‑I x , 0.1<=x<=5, which is a heterogeneous phase containing S and I2 phases; the XRD pattern thereof has characteristic peaks of the I2 phase at diffraction angles 2 theta values of 23.9+ / -0.2 and 24.3+ / -0.2. In the charging and discharging process, the pre-introduced I2 phase in the sulfur-iodine composite can occur in the form of I2 / I ‑ redox couples to rapidly and reversibly undergo redox reactions, thereby mediating the acceleration of the solid-solid conversion between the metal sulfide and S in the composite positive electrode material; meanwhile, the I2 phase can in-situ occur redox reactions with the sulfide solid electrolyte to form I2 / I ‑ nano network structures, which can chemically mediate the solid-solid conversion of the metal sulfide / S.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of all-solid-state battery technology, and more specifically, to a positive electrode active material, a composite positive electrode material, and their preparation methods and applications for all-solid-state batteries. Background Technology

[0002] With the rapid development of mobile communications, electric vehicles, and large-scale energy storage, the market demand for batteries with high energy density, high safety, and long cycle life is constantly increasing. Existing commercial lithium-ion batteries mainly use intercalated transition metal oxide cathodes and graphite anodes, and their energy density is approaching a bottleneck, making it difficult to meet the development needs of higher energy density energy storage systems. Metal-sulfur-based batteries, using elemental sulfur as the cathode and metals such as lithium or sodium as the anode, have advantages such as high theoretical energy density, low cost, and environmental friendliness, and are considered a highly promising next-generation battery system. However, despite the high theoretical energy density of metal-sulfur-based batteries, their current cycle life still falls short of practical application requirements, becoming a key factor limiting the further development of this system. Taking traditional liquid lithium-sulfur batteries as an example: they suffer from problems such as lithium polysulfide dissolution shuttle, lithium metal interface instability, and insufficient safety, resulting in rapid capacity decay, poor rate performance, and limited cycle life.

[0003] Compared with traditional systems, all-solid-state metal sulfur-based batteries use solid electrolytes instead of organic liquid electrolytes, which can fundamentally suppress polysulfide shuttle, improve battery safety, and is expected to achieve higher energy density through designs such as bipolar stacking.

[0004] All-solid-state metal-sulfur based batteries typically consist of a positive electrode composite layer, a solid electrolyte layer, and a metal negative electrode layer. Taking all-solid-state lithium-sulfur batteries as an example: existing positive electrode composite layers are mostly composed of sulfur or lithium sulfide active materials, conductive carbon, and a solid electrolyte. The conductive carbon provides the electron transport path, and the solid electrolyte provides the Li-24-metal anode. + The transport pathway involves sulfur or lithium sulfide in the electrochemical energy storage reaction. The fundamental reaction in this type of system relies on a multiphase boundary where sulfur-based active materials, conductive carbon, and a solid electrolyte are in simultaneous contact. This is due to the presence of S8, metal sulfides such as Li2S, and potentially Li2S... x Both exhibit poor electronic / ionic conductivity, and active materials far from the multiphase boundary are difficult to utilize rapidly, resulting in slow solid-solid sulfur redox reactions. Furthermore, the significant volume change of sulfur / lithium sulfide during charge and discharge disrupts the solid-solid contacts within the cathode, further hindering electron and ion transport. Existing all-solid-state lithium-sulfur battery cathodes generally suffer from insufficient rate performance and cycle stability.

[0005] To address the aforementioned issues, existing technologies primarily employ the following strategies: mechanical ball milling or liquid-phase assisted microstructuring of the cathode; using metal sulfides such as Li₂S as the initial active material and adding functional additives such as LiI, LiBr, LiVS₂, or carbon. However, these approaches still have shortcomings: First, simply increasing electronic / ionic conductivity does not fundamentally increase the density of solid-solid sulfur reaction sites; second, the spatial contact between the added medium and the sulfur-based active material is usually limited, especially in cathodes with high sulfur content and high loading; third, the soluble redox medium in the liquid electrolyte relies on liquid-phase diffusion and cannot be directly applied to all-solid-state systems.

[0006] Therefore, it is necessary to develop novel composite sulfur-based cathode materials from the perspective of sulfur-based cathode design to solve problems such as insufficient density of solid-solid reaction sites and solid-solid contact.

[0007] In view of this, the present invention is hereby proposed. Summary of the Invention

[0008] To address issues such as insufficient density of solid-solid reaction sites and solid-solid contact, the primary objective of this invention is to provide a positive electrode active material for all-solid-state batteries, employing the general formula S... 10-x -I x The sulfur-iodine complex, during charge and discharge, the pre-introduced I2 phase in the sulfur-iodine complex can achieve an I2 / I2 ratio. - A rapid and reversible redox reaction occurs in the form of a redox couple, thereby mediating and accelerating the solid-solid conversion between metal sulfides and sulfur in the composite cathode material; simultaneously, the I2 phase reacts in situ with the sulfide solid electrolyte to form I2 / I2 / I2. - Nanoscale network structure, which acts as I2 / I - Solid-solid redox media can undergo reversible redox reactions during charging and discharging, chemically mediating the solid-solid transformation of metal sulfides / S.

[0009] The second objective of this invention is to provide a composite cathode material in which the S phase and I2 phase in the sulfur-iodine composite within the porous structure are uniformly distributed at the nanoscale. This ensures effective contact between the dielectric and sulfur during long-term cycling, thus facilitating solid-solid contact. This solves the problem in the prior art where significant volume changes in sulfur / lithium sulfide during charge and discharge disrupt the solid-solid contact within the cathode, thereby hindering electron and ion transport.

[0010] The third objective of this invention is to provide a method for preparing composite cathode materials.

[0011] The fourth objective of this invention is to provide an all-solid-state battery.

[0012] The fifth objective of this invention is to provide an electrical appliance.

[0013] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: This invention first provides a positive electrode active material for all-solid-state batteries, comprising materials with the general formula S 10-x -I x The sulfur-iodine complex, wherein 0.1 ≤ x ≤ 5; the sulfur-iodine complex is heterogeneous and contains an S phase and an I2 phase; the X-ray powder diffraction pattern of the sulfur-iodine complex has characteristic peaks of the I2 phase at diffraction angles 2θ of 23.9° ± 0.2° and 24.3° ± 0.2°.

[0014] Furthermore, the X-ray powder diffraction pattern of the sulfur-iodine complex exhibits the characteristic peaks of the S phase at diffraction angles 2θ of 23.0°±0.2°, 25.8°±0.2°, and 27.7°±0.2°.

[0015] Furthermore, the cryo-electron microscopy image of the sulfur-iodine complex contains lattice fringes with a crystal plane spacing of 0.405 nm ± 0.005 nm.

[0016] Furthermore, the cryo-electron microscopy image of the sulfur-iodine complex contains lattice fringes with a crystal plane spacing of 0.365 nm ± 0.005 nm.

[0017] Furthermore, the cryo-electron microscopy image of the sulfur-iodine complex includes the (220) crystal plane of the S phase and the (200) crystal plane of the I2 phase.

[0018] Furthermore, 0.5 ≤ x ≤ 4.

[0019] Furthermore, 1.43 ≤ x ≤ 4.

[0020] This invention further provides a composite cathode material, comprising the above-mentioned cathode active material for all-solid-state batteries and a porous conductive carbon material; wherein the porous conductive carbon material is a carbon material with a porous structure and conductivity; at least a portion of the sulfur-iodine complex is located within the porous structure of the porous conductive carbon material, forming an amorphous structure; during the charge-discharge process, the I2 phase in the sulfur-iodine complex reacts with I... - The reversible redox reaction between the metal sulfides and sulfur in the composite cathode material accelerates the solid-solid conversion through the reversible redox reaction.

[0021] Furthermore, the mass ratio of the positive electrode active material for the all-solid-state battery to the porous conductive carbon material is 55~95:5~45.

[0022] Furthermore, the porous conductive carbon material includes at least one of mesoporous carbon, high specific surface area conductive carbon black, and structured porous carbon, wherein the structured porous carbon has a hierarchical pore structure.

[0023] Furthermore, the structured porous carbon is an aerogel material or a hollow structure material.

[0024] Furthermore, the high specific surface area conductive carbon black includes those with a specific surface area ≥ 50 m². 2 / g of carbon black.

[0025] Furthermore, the composite cathode material also includes a solid electrolyte.

[0026] Furthermore, the solid electrolyte includes at least one of sulfide solid electrolyte, halide solid electrolyte, oxide solid electrolyte, and halide oxide solid electrolyte.

[0027] Furthermore, the mass fraction of the solid electrolyte is ≤50%.

[0028] Furthermore, the composite cathode material also includes a conductive agent.

[0029] Furthermore, the mass fraction of the conductive agent is ≤25%.

[0030] The present invention further provides a method for preparing a composite cathode material, comprising the following steps: (a) mixing the cathode active material for all-solid-state batteries with a porous conductive carbon material, or mixing elemental sulfur and elemental iodine with a porous conductive carbon material, and then heating and melting the mixture so that the molten liquid cathode active material for all-solid-state batteries or the liquid mixture of elemental sulfur and elemental iodine enters the pore structure of the porous conductive carbon material, and then cooling the mixture.

[0031] Furthermore, after step (a), the following step (b) is included: mixing the cooled material with a solid electrolyte.

[0032] Furthermore, during the mixing process in step (b), when the solid electrolyte contains a sulfide solid electrolyte, the sulfide solid electrolyte comes into contact with the I2 phase in the cooled material and undergoes an in-situ redox reaction, causing part of the I2 phase to transform into LiI nanoparticles, forming an I2 / I... - Nanoscale network structure, which acts as I2 / I - A solid-solid redox medium is pre-introduced into the composite cathode material; during charge and discharge, the I2 / I2 in the composite cathode material... - The nanonetwork structure undergoes reversible redox reactions, further enhancing the chemically mediated solid-solid transformation of metal sulfides / S.

[0033] Furthermore, the average particle size of the LiI nanoparticles is 2~50 nm.

[0034] Furthermore, a conductive agent is added during the mixing process in step (b).

[0035] The present invention also provides an all-solid-state battery, comprising a positive electrode composite layer, a solid electrolyte layer and a negative electrode layer; wherein the positive electrode composite layer contains the aforementioned positive electrode material.

[0036] Furthermore, the solid electrolyte layer is made of inorganic solid electrolyte and / or polymer solid electrolyte, wherein the inorganic solid electrolyte includes at least one of sulfide solid electrolyte, halide solid electrolyte, oxide solid electrolyte and oxyhalide solid electrolyte.

[0037] Furthermore, the material of the negative electrode layer includes at least one of lithium and its alloys, sodium and its alloys, metallic potassium, and metallic aluminum.

[0038] The present invention also provides an electrical device comprising the above-described all-solid-state battery.

[0039] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The positive electrode active material for all-solid-state batteries provided by the present invention adopts the general formula S 10-x -I x The sulfur-iodine complex, during charge and discharge, the pre-introduced I2 phase in the sulfur-iodine complex can achieve an I2 / I2 ratio. - A rapid and reversible redox reaction occurs in the form of a redox couple, thereby mediating and accelerating the solid-solid conversion between metal sulfides and sulfur in the composite cathode material. Furthermore, when a sulfide solid electrolyte is used as the cathode in an all-solid-state battery, the I2 phase can undergo an in-situ redox reaction with the sulfide solid electrolyte to form I2 / I... - Nanoscale network structure, which acts as I2 / I - Solid-solid redox media can undergo reversible redox reactions during charge and discharge, further enhancing the chemically mediated solid-solid conversion of metal sulfides / S.

[0040] (2) The composite cathode material provided by this invention provides a new solid-solid reaction kinetic control method for all-solid metal-sulfur-based batteries: by confining and combining sulfur-iodine composites within the porous structure of porous conductive carbon materials to form an amorphous or glassy sulfur / iodine nanocomposite structure, and utilizing the pre-introduced I2 / I - Redox media promote solid-solid conversion of sulfur species, providing a new technical approach to solve the problem of slow conversion reaction that is common in all-solid-state metal-sulfur-based batteries.

[0041] (3) The composite cathode material provided by this invention can effectively improve the utilization rate and high-rate performance of sulfur-based active materials: This invention increases the number of sulfur / iodine contact interfaces and redox-mediated sites, and through I2 / I - The mediated reaction reduces the dependence of metal sulfide oxidation on finite multiphase interfaces. Therefore, even at higher charge rates and larger current densities, the sulfur species conversion reaction can still be maintained relatively quickly inside the cathode. Taking an all-solid-state lithium-sulfur battery containing the sulfur-iodine composite S8I2 as an example, at 25°C, it exhibits a higher reversible capacity under high-rate conditions compared to pure sulfur / carbon cathodes or metal sulfide-metal iodide cathodes.

[0042] (4) The composite cathode material provided by this invention is beneficial for constructing sulfur-based cathodes with high active material ratio and high areal loading: Traditional all-solid-state metal-sulfur-based cathodes usually require the addition of a high proportion of conductive agents and solid electrolytes to ensure sufficient electron and ion transport, which reduces the mass percentage of sulfur active material in the cathode and weakens the actual mass energy density of the battery. This invention expands the effective reaction area by pre-introducing redox media and constructing multi-interface synergistic reaction pathways. Therefore, when increasing the active material ratio or increasing the cathode areal loading, it is still beneficial to maintain the effective conversion of active material. Taking an all-solid-state lithium-sulfur battery containing the cathode active material sulfur-iodine composite S8I2 as an example, the mass percentage of active material in the cathode can be increased to 60wt%~70wt%.

[0043] (5) The composite cathode material provided by this invention can effectively improve the reversibility and long-cycle stability of the cathode conversion reaction: the composite cathode material can maintain effective contact between the medium and sulfur during long-term cycling, reduce solid-solid contact failure, and improve the reaction reversibility, capacity retention and long-cycle stability of the all-solid metal-sulfur based battery; at the same time, the in-situ reaction of I2 with the sulfide electrolyte prevents further decomposition of the sulfide electrolyte, further improving the cycle life of the battery. Taking the all-solid lithium-sulfur battery containing the cathode active material sulfur-iodine composite S8I2 as an example, the battery can achieve 9000 cycles of high stability.

[0044] (6) The composite cathode material provided by this invention is applicable to all-solid-state metal-sulfur based batteries. This invention addresses common problems in solid-state sulfur conversion reactions, such as insufficient effective multiphase interfaces, slow reaction kinetics, and easy failure of solid-solid contacts. These problems are not unique to all-solid-state lithium-sulfur batteries. For all-solid-state metal-sulfur based batteries with metals such as sodium as anodes, the cathode also involves solid-solid conversion between sulfur and the corresponding metal sulfides, as well as insufficient kinetics. Therefore, provided that the reaction potential of the redox medium, the metal ion transport properties, and the interfacial chemical stability meet the requirements, the porous confined nanocomposite, pre-introduced solid redox medium, and multi-interface synergistic reaction scheme proposed in this invention can serve as a general design principle for other all-solid-state metal-sulfur based batteries.

[0045] (7) The method for preparing the composite cathode material provided by the present invention is simple and facilitates large-scale preparation: S is obtained by low-temperature melting of raw materials, impregnation of porous conductive carbon materials and cooling solidification. 10-x -I x The porous conductive carbon material composite material does not require complex high-temperature synthesis, special chemical vapor deposition, or multi-step surface coating processes. The resulting material can be further composited with sulfide solid electrolytes through common solid-state battery manufacturing processes such as mixing, ball milling, and pressing, exhibiting good process feasibility. Therefore, this invention is advantageous for integration with existing powder preparation, composite electrode processing, and dry pressing processes for all-solid-state metal-sulfur-based batteries, and has the potential for further scale-up fabrication. Attached Figure Description

[0046] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0047] Figure 1 XRD pattern of the sulfur-iodine complex with general formula S8I2 obtained in Example 1 of this invention; Figure 2 Raman spectrum of the sulfur-iodine complex with general formula S8I2 obtained in Example 1 of this invention; Figure 3 Cryo-transmission electron microscopy image and selected area electron diffraction pattern of the sulfur-iodine complex with the general formula S8I2 prepared in Example 1 of the present invention. Figure 4 The XRD pattern of the first composite cathode material, namely the S8I2 / KB composite material, prepared in Example 2 of this invention; Figure 5 Fast charging performance test diagram of the all-solid-state lithium-sulfur battery prepared in Example 2 of the present invention at 25°C; Figure 6 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Example 2 of this invention; Figure 7 Cyclic performance test diagram of the all-solid-state lithium-sulfur battery prepared in Example 3 of the present invention at 25°C; Figure 8 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Example 3 of this invention; Figure 9 Cycling performance test diagram of the all-solid-state lithium-sulfur battery prepared in Example 4 of the present invention at 25°C; Figure 10 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Example 4 of this invention; Figure 11 Transmission electron microscope image of the second composite cathode material prepared in Example 5 of this invention; Figure 12 The cycle performance test diagram of the all-solid-state lithium-sulfur battery prepared in Example 5 of the present invention at 25°C; Figure 13 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Example 5 of this invention; Figure 14 Cycling performance test diagram of the all-solid-state lithium-sulfur battery prepared in Example 6 of the present invention at 25°C; Figure 15 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Example 6 of this invention; Figure 16 The fast charging performance test diagram of the all-solid-state lithium-sulfur battery prepared in Comparative Example 1 provided by the present invention at 25°C. Figure 17 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Comparative Example 1 is provided for the present invention. Figure 18 The fast charging performance test diagram of the all-solid-state lithium-sulfur battery prepared in Comparative Example 2 provided by the present invention at 25°C. Figure 19 The specific capacity-voltage curve of the all-solid-state lithium-sulfur battery prepared in Comparative Example 2 is provided for the present invention. Detailed Implementation

[0048] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0049] In a first aspect, the present invention provides a sulfur-based positive electrode active material for all-solid-state batteries, comprising a sulfur-based positive electrode active material of the general formula S0. 10-x -I x The sulfur-iodine complex, wherein 0.1≤x≤5, for example 0.1, 0.3, 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5.

[0050] The sulfur-iodine complex is heterogeneous, containing both an S phase and an I2 phase. That is, the sulfur-iodine complex is a two-phase composite in which the S and I2 phases are distributed at the nanoscale.

[0051] It is understandable that the sulfur-iodine complex is neither a compound nor a solid solution, but rather a combination of two phases: S and I2.

[0052] The X-ray powder diffraction pattern of the sulfur-iodine complex shows characteristic peaks of the I2 phase at diffraction angles of 2θ values ​​of 23.9°±0.2°, such as 23.7°, 23.8°, 23.9°, 24.0°, and 24.1°, and at diffraction angles of 2θ values ​​of 24.3°±0.2°, such as 24.1°, 24.2°, 24.3°, 24.4°, and 24.5°. This demonstrates that the sulfur-iodine complex is heterogeneous.

[0053] This invention utilizes the general formula S 10-x -I x The sulfur-iodine complex, during charge and discharge, the pre-introduced I2 phase in the sulfur-iodine complex can achieve an I2 / I2 ratio. - A rapid and reversible redox reaction occurs in the form of a redox couple, thereby mediating and accelerating the solid-solid conversion between metal sulfides and sulfur in the composite cathode material; simultaneously, the I2 phase reacts in situ with the sulfide solid electrolyte to form I2 / I2 / I2. - Nanoscale network structure, which acts as I2 / I - Solid-solid redox media can undergo reversible redox reactions during charging and discharging, chemically mediating the solid-solid transformation of metal sulfides / S.

[0054] It is understandable that when the material of the negative electrode layer includes lithium and its alloys, the metal sulfide includes Li2S; when the material of the negative electrode layer includes sodium and its alloys, the metal sulfide includes Na2S; and so on.

[0055] In some specific embodiments, the X-ray powder diffraction pattern of the sulfur-iodine complex exhibits characteristic peaks of the S phase at diffraction angles 2θ of 23.0°±0.2° (e.g., 22.8°, 22.9°, 23.0°, 23.1°, or 23.2°), 25.8°±0.2° (e.g., 25.6°, 25.7°, 25.8°, 25.9°, or 26.0°), and 27.7°±0.2° (e.g., 27.5°, 27.6°, 27.7°, 27.8°, or 27.9°).

[0056] In some specific embodiments, the cryo-electron microscopy image of the sulfur-iodine complex contains lattice fringes with interplanar spacing of 0.405 nm ± 0.005 nm, such as 0.400 nm, 0.402 nm, 0.405 nm, 0.408 nm, or 0.410 nm.

[0057] In some specific embodiments, the cryo-electron microscopy image of the sulfur-iodine complex contains lattice fringes with a crystal plane spacing of 0.365 nm ± 0.005 nm, such as 0.360 nm, 0.362 nm, 0.365 nm, 0.368 nm, or 0.370 nm.

[0058] In some specific embodiments, the cryo-electron microscopy image of the sulfur-iodine complex includes the (220) crystal plane of the S phase and the (200) crystal plane of the I2 phase.

[0059] The lattice fringes with a spacing of 0.405 nm ± 0.005 nm, after being calibrated by Fourier transform, belong to the (220) crystal plane of the S phase of the sulfur-iodine complex.

[0060] The lattice fringes with a spacing of 0.365 nm ± 0.005 nm, after being calibrated by Fourier transform, belong to the (200) crystal plane of the I2 phase of the sulfur-iodine complex.

[0061] The XRD and cryo-electron microscopy results above further confirm the existence of the S phase and I2 phase, that is, the sulfur-iodine complex is heterogeneous.

[0062] As a preferred value, 0.5≤x≤4.

[0063] Further optimization yields 1.43≤x≤4.

[0064] In some specific embodiments, the positive electrode active material includes the sulfur-iodine complex of at least one of the general formulas S8I2, S7I3 and S6I4.

[0065] In some specific embodiments, the preparation method of the above-mentioned positive electrode active material for all-solid-state batteries includes: mixing and grinding elemental sulfur powder and elemental iodine in stoichiometric ratio, heating in a sealed reaction vessel, and then naturally cooling to obtain a heterogeneous sulfur-iodine composite containing S phase and I2 phase. Under sealed conditions, the vapor pressure of iodine is very high, and due to the difference in molecular size, the two phases separate during cooling. This preparation method is simple and has a short process, which is conducive to mass production. Preferably, the heating temperature is 80~150℃, for example 80℃, 90℃, 100℃, 110℃, 120℃, 130℃, 140℃, 150℃; the heating holding time is 4~20h, for example 4h, 5h, 6h, 8h, 10h, 12h, 15h, 18h, 20h. The sealed reaction vessel includes a sealed tube, such as a sealed glass tube, or a sealed container, wherein the sealed glass tube is vacuum-sealed; the sealed container may be vacuum-sealed or directly sealed without vacuuming.

[0066] Secondly, the present invention provides a composite cathode material, including the above-mentioned cathode active material for all-solid-state batteries, and a porous conductive carbon material.

[0067] The porous conductive carbon material is a carbon material with a porous structure and conductivity.

[0068] At least a portion of the sulfur-iodine complex is located within the porous structure of the porous conductive carbon material, forming an amorphous structure; and the S phase and the I2 phase in the sulfur-iodine complex are uniformly distributed at the nanoscale within the porous structure.

[0069] During the charge-discharge process, the I2 phase in the sulfur-iodine composite material reacts with I... - The reversible redox reaction between the metal sulfides and sulfur in the composite cathode material accelerates the solid-solid conversion through the reversible redox reaction.

[0070] That is, during the charging and discharging process, the pre-introduced I2 phase can achieve an I2 / I ratio. - A rapid, reversible redox reaction occurs in the form of a redox couple. I₂ / I - The oxidized iodine species formed during the charging process by the redox couple can further chemically oxidize adjacent metal sulfides or low-valence sulfur species, promoting their conversion into high-valence sulfur species or elemental sulfur. This invention accelerates the solid-solid conversion between metal sulfides and sulfur in composite cathode materials through a reversible redox reaction, solving the problem of slow solid-solid sulfur redox reactions in existing technologies.

[0071] Furthermore, the composite cathode material provided by this invention exhibits a nanoscale uniform distribution of the S and I2 phases in the sulfur-iodine complex within its porous structure. This ensures effective contact between the dielectric and sulfur during long-term cycling, thus facilitating solid-solid contact. This solves the problem in existing technologies where significant volume changes in sulfur / lithium sulfide during charge and discharge disrupt the solid-solid contact within the cathode, thereby hindering electron and ion transport.

[0072] In some specific embodiments, the mass ratio of the positive electrode active material for the all-solid-state battery to the porous conductive carbon material is 55~95:5~45, for example 95:5, 92:8, 90:10, 88:12, 85:15, 82:18, 80:20, 75:25, 70:30, 65:35, 60:40 or 55:45.

[0073] In some specific embodiments, the porous conductive carbon material includes at least one of mesoporous carbon, high specific surface area conductive carbon black, and structured porous carbon, wherein the structured porous carbon has a hierarchical pore structure.

[0074] In some specific embodiments, the structured porous carbon is an aerogel material or a hollow structural material.

[0075] In some specific embodiments, the high specific surface area conductive carbon black includes those with a specific surface area ≥ 50 m². 2 / g for example 50m 2 / g, 100m 2 / g、200m 2 / g、400m 2 / g、500m 2 / g、600m 2 / g、800m 2 / g, 1000m 2 / g、1300m 2 / g or 1500m 2 / g of carbon black, preferably with a specific surface area ≥200m² 2 / g of Ketjen black is equivalent to KB.

[0076] In some specific embodiments, the composite cathode material also includes a solid electrolyte.

[0077] In some specific embodiments, the solid electrolyte includes at least one of sulfide solid electrolyte, halide solid electrolyte, oxide solid electrolyte, and halide oxide solid electrolyte.

[0078] In some specific embodiments, the mass fraction of the solid electrolyte is ≤50%, for example, 1%, 2%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 25%, 30%, 35%, 40%, 45% or 50%.

[0079] In some specific embodiments, the composite cathode material also includes a conductive agent.

[0080] In some specific embodiments, the conductive agent includes, but is not limited to, at least one of conductive carbon black, carbon nanotubes, carbon nanofibers, graphene, conductive graphite, acetylene black, and vapor-grown carbon fibers.

[0081] In some specific embodiments, the conductive agent accounts for ≤25% by mass, for example 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 13%, 15%, 18%, 20%, 22% or 25%.

[0082] In some specific embodiments, the ratio of the total mass of the positive electrode active material and the porous conductive carbon material used in the all-solid-state battery to the mass of the solid electrolyte and the mass of the conductive agent is 40~97:3~50:0~10, for example 80:15:5, 70:20:10, 85:12:3, 60:30:10, 90:8:2 or 75:20:5.

[0083] In some specific embodiments, the all-solid-state battery containing the composite cathode material exhibits a specific capacity ≥600 mAh·g at a temperature of 25°C, a charge rate of 10C, and a discharge rate of 2C. -1 Preferred specific capacity ≥700mAh·g -1 .

[0084] Thirdly, the present invention provides a method for preparing a composite cathode material, comprising the following steps: (a) mixing the cathode active material for all-solid-state batteries with a porous conductive carbon material, or mixing elemental sulfur and elemental iodine with a porous conductive carbon material; then heating and melting the mixture to allow the molten liquid cathode active material for all-solid-state batteries or the liquid mixture of elemental sulfur and elemental iodine to enter the pore structure of the porous conductive carbon material, and then naturally cooling it to room temperature.

[0085] This invention constructs S 10-x -I x The carbon composite cathode material utilizes the confinement effect of the porous conductive carbon material's pore structure to homogenize the S and I2 phases in the sulfur-iodine composite at the nanoscale, forming an amorphous S phase. 10-x -I xA carbon-based composite. The composite cathode material prepared using the above method exhibits fast-charging performance and long-cycle stability.

[0086] Specifically, this invention mixes elemental sulfur and elemental iodine in a predetermined ratio and heats them to form a liquid mixture. The liquid mixture is then nanoscale confined within the porous structure of a porous conductive carbon material. After entering the porous structure, the liquid mixture is restricted by the pore space during cooling, inhibiting long-range diffusion, phase separation, and crystal growth of sulfur and iodine. This results in an amorphous sulfur-iodine composite with uniformly distributed S and I2 phases at the nanoscale. The S and I2 phases form a close nanoscale contact before battery assembly. During charging and discharging, the pre-introduced I2 phase can achieve an I2 / I2 ratio... - A rapid, reversible redox reaction occurs in the form of a redox couple. I₂ / I - The oxidized iodine species formed during the charging process of the redox couple can further chemically oxidize adjacent metal sulfides or low-valence sulfur species, promoting their transformation into high-valence sulfur species or elemental sulfur.

[0087] In some specific implementations, the mixing method in step (a) includes, but is not limited to, ball milling, high-temperature diffusion, grinding, etc.

[0088] In some specific embodiments, the heating and melting in step (a) is carried out in a sealed reaction vessel, wherein the sealed reaction vessel includes a sealed tube such as a sealed quartz tube or a sealed tank.

[0089] In some specific embodiments, after step (a), the following step (b) is further included: mixing the cooled material from step (a) with a solid electrolyte.

[0090] During the mixing process in step (b), when the solid electrolyte contains a sulfide solid electrolyte, the sulfide solid electrolyte comes into contact with the I2 phase in the cooled material and undergoes an in-situ redox reaction, causing part of the I2 phase to be converted into LiI nanoparticles, forming a uniformly dispersed I2 / I2 / LiI nanoparticle. - Nanoscale network structure, which acts as I2 / I - A solid-solid redox medium is pre-introduced into the composite cathode material; during charge and discharge, the I2 / I2 in the composite cathode material... - The nano-network structure undergoes reversible redox reactions, chemically mediating solid-solid transformation of metal sulfide / S.

[0091] In traditional all-solid-state lithium-sulfur batteries, the reaction of sulfur or metal sulfides typically requires simultaneous contact between the sulfur active material, the electronic conductor, and the solid electrolyte. Due to the limited number of such multiphase reaction interfaces, sulfur or metal sulfides located far from these interfaces struggle to simultaneously gain electrons and Li.+ The transport channel results in slow solid-solid reaction kinetics. The pre-introduction of I₂ / I₂ in this invention... - The solid-solid redox medium mechanism transforms the reaction from solely relying on the multiphase interface directly formed by the sulfur-containing active material, conductive carbon, and solid electrolyte into a synergistic interfacial reaction involving multiple interfaces. This increases the density of reactive sites and effectively improves the battery's rate performance.

[0092] Pre-introduction refers to the process of introducing I before the positive electrode material is charged and discharged. - It is pre-introduced into the composite cathode material.

[0093] By pre-introducing I2 / I - Solid-solid redox media enable high-rate metal-sulfur-based batteries.

[0094] Under high-rate charging conditions, I2 / I - Electrochemical couples can chemically mediate solid-solid transformations of metal sulfides / S, thereby transforming the traditionally slow sulfur reaction dependent on multiphase boundaries into I₂ / I₂ reactions. - Redox-mediated concerted reaction.

[0095] With S 10-x -I x Taking a solid-state lithium-sulfur battery as an example, the main reaction formula is as follows: xI2+Li 5.5 PS 4.5 Cl 1.5 →2xLiI+Li 5.5-2x PS 4.5-x Cl 1.5 +xS. This formula corresponds to the in-situ reaction of iodine with the sulfide electrolyte in the positive electrode to form LiI, and is used to explain the formation of the LiI / I2 nano-distribution network.

[0096] I₂ + Li₂S → 2LiI + S. This equation corresponds to the mediated reaction of I₂ chemical oxidation of Li₂S and is used to explain the I₂ / I₂ reaction. - The reaction mechanism by which the electron couple promotes the solid-phase Li2S / S conversion.

[0097] This invention pre-introduces I2 / I into the composite cathode material. - Solid-solid redox media transforms traditional multiphase interface-constrained reactions into multi-interface synergistic reactions, thereby improving the rate performance of all-solid-state sulfur-based batteries.

[0098] Furthermore, this invention utilizes the in-situ reaction of the I2 phase with the sulfide solid electrolyte to construct an I2 / I phase that extends through the positive electrode. - Nanoscale network structures not only improve the rate performance of batteries, but also contribute to long-cycle stability.

[0099] This invention reveals that when the cooled material is mixed with a solid electrolyte to form a composite cathode material in step (b), a portion of the I2 phase can spontaneously react with the sulfide solid electrolyte to generate LiI nanoparticles in situ. This forms a spatially continuous or widely distributed LiI / I2 redox nanonetwork within the composite cathode. This not only helps maintain effective contact between sulfur species and the redox medium during long-term cycling but also inhibits further redox decomposition of the electrolyte, thus contributing to the long-term cycle stability of the battery.

[0100] In some specific embodiments, the average particle size of the LiI nanoparticles is 2~50nm, for example 2nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, and 50nm.

[0101] In some specific embodiments, a conductive agent is also added during the mixing process in step (b).

[0102] In some specific embodiments, the mixing method in step (b) includes, but is not limited to, grinding, ball milling, vibratory milling, and high-speed stirring.

[0103] Fourthly, the present invention provides an all-solid-state battery, comprising a positive electrode composite layer, a solid electrolyte layer, and a negative electrode layer. The positive electrode composite layer contains the aforementioned positive electrode material.

[0104] The aforementioned cathode materials, when used in all-solid-state batteries, offer advantages such as high energy density, low cost, excellent rate performance, and long-cycle stability.

[0105] In some specific embodiments, the mass fraction of the sulfur-iodine complex in the positive electrode composite layer is 60% to 75%, for example, 60%, 65%, 68%, 70%, 72% or 75%.

[0106] In some specific embodiments, the solid electrolyte layer is made of inorganic solid electrolyte and / or polymer solid electrolyte.

[0107] In some specific embodiments, the inorganic solid electrolyte includes at least one of sulfide solid electrolytes, halide solid electrolytes, oxide solid electrolytes, and oxyhalide solid electrolytes.

[0108] The aforementioned cathode materials can be applied to various metal-sulfur-based battery systems.

[0109] In some specific embodiments, the material of the negative electrode layer includes at least one of lithium and its alloys, sodium and its alloys, metallic potassium, and metallic aluminum.

[0110] In some specific embodiments, the all-solid-state battery includes an all-solid-state lithium-sulfur battery.

[0111] Fifthly, the present invention provides an electrical device comprising the aforementioned all-solid-state battery.

[0112] Based on S 10-x -I x With its advantages of high energy density, high rate capability, and long cycle stability, all-solid-state batteries can be applied to various application scenarios such as extreme temperatures and drones. This invention does not impose any special restrictions on the electrical equipment.

[0113] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0114] Example 1 The positive electrode active material provided in this embodiment for all-solid-state batteries is a sulfur-iodine composite with the general formula S8I2, i.e., x=2. The preparation method is as follows: elemental sulfur and elemental iodine are weighed according to the stoichiometric ratio of S8I2, mixed and ground, placed in a sealed glass tube, heated to 80°C and kept at that temperature for 10 hours, then naturally cooled to room temperature, taken out and ground into powder to obtain the sulfur-iodine composite with the general formula S8I2.

[0115] The XRD pattern, Raman pattern, cryo-transmission electron microscope image, and selected area electron diffraction pattern of the sulfur-iodine complex with the general formula S8I2 are shown below. Figure 1 , Figure 2 and Figure 3 As shown.

[0116] Figure 1 The XRD patterns show that the sulfur-iodine complex contains an S phase (α-S8 is a specific crystal phase type of the S phase) and an I2 phase, which are heterogeneous. Specifically, the X-ray powder diffraction pattern of the sulfur-iodine complex has characteristic peaks of the I2 phase at diffraction angles of 2θ of 23.9° and 24.3°, and characteristic peaks of the S phase at diffraction angles of 2θ of 23.0°, 25.8° and 27.7°.

[0117] Figure 2 The Raman spectrum also showed that the sulfur-iodine complex contained both S and I2 phases.

[0118] Figure 3The cryo-transmission electron microscopy images show that the sulfur-iodine complex of general formula S8I2 contains nanoscale S and I2 phases. Specifically, the cryo-electron microscopy images of the sulfur-iodine complex contain lattice fringes with a crystal plane spacing of 0.405 nm, which, after Fourier transform calibration, belong to the (220) crystal plane of the S phase of the sulfur-iodine complex. The cryo-electron microscopy images of the sulfur-iodine complex contain lattice fringes with a crystal plane spacing of 0.365 nm, which, after Fourier transform calibration, belong to the (200) crystal plane of the I2 phase of the sulfur-iodine complex.

[0119] Example 2 The method for preparing the composite cathode material provided in this embodiment includes the following steps: The sulfur-iodine complex with the general formula S8I2 obtained in Example 1 was mixed with a specific surface area of ​​1300 m². 2 / g of porous conductive carbon material, Ketjen black (KB), was mixed at a mass ratio of 75:25 and placed in a sealed quartz tube. The mixture was heated to 100°C and held at this temperature for 12 hours, allowing the molten sulfur-iodine composite S8I2 to enter the porous structure of the Ketjen black. After cooling, the S8I2 / KB composite material was obtained, which is the first composite cathode material. At least a portion of the sulfur-iodine composite is located within the porous structure of the porous conductive carbon material. The XRD pattern of the S8I2 / KB composite material, i.e., the first composite cathode material, is shown below. Figure 4 As shown, Figure 4 This indicates that the composite cathode material has an amorphous structure.

[0120] Furthermore, the first composite cathode material mentioned above, namely the S8I2 / KB composite material, is combined with the sulfide solid electrolyte Li... 5.5 PS 4.5 Cl 1.5 The sulfide solid electrolyte and the conductive agent Super P were mixed at a mass ratio of 4:5:1 (i.e., the mass fraction of the sulfide solid electrolyte was 50% and the mass fraction of the conductive agent was 10%), and then placed in a zirconia ball mill jar, wherein the mass ratio of zirconia beads to the material being milled was 40:1. The ball mill jar was sealed under an argon atmosphere. The ball mill jar was then placed in a planetary ball mill and milled at 500 rpm for 20 hours to ensure uniform mixing, thus obtaining a cathode material for solid-state lithium-sulfur batteries, namely the second composite cathode material. In the preparation process of this second composite cathode material, the I2 phase in S8I2 / KB reacts with the contacting Li... 5.5 PS 4.5 Cl 1.5 An in-situ reaction occurred, generating LiI nanoparticles.

[0121] This embodiment also provides a method for preparing an all-solid-state battery, including the following steps: under an argon atmosphere, 80 mg of Li 5.5 PS 4.5 Cl1.5 The electrolyte was placed in a 10 mm diameter PEEK cylinder and pressed at both ends with custom-made Ti pillars under a pressure of 125 MPa for 1 min to form a solid electrolyte layer. Then, the S8I2 loading was set to 1.1 mg·cm³. -2 (Based on S8I2) The cathode material for solid-state lithium-sulfur batteries, namely the second composite cathode material, prepared above, is uniformly spread on top of the solid electrolyte layer and pressed at 312 MPa for 3 minutes to form a cathode composite layer. Then, on the other side of the solid electrolyte layer, an indium foil (9 mm in diameter) and a lithium foil (7 mm in diameter) are placed. The mold battery is then placed in a custom-made stainless steel casing and a pressure of 64 MPa is applied to obtain an all-solid-state lithium-sulfur battery.

[0122] The all-solid-state lithium-sulfur battery prepared in this embodiment was subjected to the following performance tests: The battery was placed in a 25°C constant temperature chamber, and constant current charge-discharge tests were performed on a NEWARE battery testing system. Based on the theoretical specific capacity of S8I2 (abbreviated as S / I), 1C was defined as 945 mA·g. -1 S / I The specific capacity and rate of increase were calculated based on the mass of S8I2. The test results are as follows: Figure 5 and Figure 6 As shown, the battery still exhibits a high specific capacity of 851.9 mAh·g at a charging rate of 10C and a discharging rate of 2C. -1 S / I Even at a charge rate of 24C and a discharge rate of 2C, the battery still maintains a high specific capacity of 474.7 mAh·g. -1 S / I .

[0123] Example 3 The only difference between the all-solid-state battery preparation method provided in this embodiment and that in Embodiment 2 is that: Li 5.5 PS 4.5 Cl 1.5 Replace with an equal mass of 3Li2S-4.5LiI-2.5B2S3-0.5P2S5 (other materials such as composite cathode materials are the same as in Example 2).

[0124] The all-solid-state lithium-sulfur battery prepared in this embodiment was subjected to the following performance tests: The battery was placed in an oven at 25°C, and a constant current charge-discharge test was performed on a NEWARE battery testing system. The test results are as follows. Figure 7 and Figure 8 As shown, at a charge / discharge rate of 5C, the battery not only has a high specific capacity of 898.8 mAh·g, but also... -1 S / I Moreover, it has extremely high long-cycle stability, with a capacity retention rate of 92.0% after 3400 battery cycles.

[0125] Example 4 The difference between the all-solid-state battery preparation method provided in this embodiment and that in Embodiment 2 is that: Li 5.5 PS 4.5 Cl 1.5 Replace with an equal mass of 3Li₂S⁻⁴⁵LiI⁻⁂⁵B₂S₃⁻⁰.⁵P₂S₅, and adjust the S₈I₂ loading to 10.0 mg·cm⁻¹. -2 (Based on S8I2) (Other materials such as composite cathode materials are the same as in Example 2).

[0126] The all-solid-state lithium-sulfur battery prepared in this embodiment was subjected to the following performance tests: The battery was placed in an oven at 25°C, and a constant current charge-discharge test was performed on a NEWARE battery testing system. The test results are as follows. Figure 9 and Figure 10 As shown, the battery operates at 0.47 mA·cm -2 At a current density of 1023.3 mAh·g, it exhibits a performance of 1023.3 mAh·g. -1 S / I (i.e., 10.2 mAh·cm) -2 It boasts a high specific capacity; even at 0.1C, it can still deliver 931.4 mAh·g. -1 S / I (i.e., 9.3 mAh·cm) -2 The S8I2 composite cathode exhibits a high specific capacity and retains 87.9% of its capacity after 100 battery cycles. This demonstrates that even with extremely high active material loading, the S8I2 composite cathode still demonstrates significant capacity and high capacity retention.

[0127] Example 5 The difference between the preparation method of the second composite cathode material provided in this embodiment and that in Embodiment 2 is that: the S8I2 / KB composite material and the sulfide solid electrolyte Li are combined. 5.5 PS 4.5 Cl 1.5 The mass ratio of the conductive agent Super P was replaced with 6.667:2.83:0.503, meaning the mass fraction of the sulfide solid electrolyte was 28.3% and the mass fraction of the conductive agent was 5.03%. During the preparation of this second composite cathode material, the I2 phase in S8I2 / KB reacts with the contacting Li... 5.5 PS 4.5 Cl 1.5 An in-situ reaction occurred, generating LiI nanoparticles. The transmission electron microscopy (TEM) results of this second composite cathode material are as follows: Figure 11 As shown, the average particle size of the LiI nanoparticles is 7 nm.

[0128] Using the second composite cathode material obtained in this embodiment, an all-solid-state lithium-sulfur battery was prepared basically according to the preparation method of the all-solid-state battery in Example 2, the difference being: Li 5.5 PS 4.5 Cl 1.5 Replace with an equal mass of 3Li₂S⁻⁴⁵LiI⁻⁂⁵B₂S₃⁻⁰.⁵P₂S₅, and adjust the S₈I₂ loading to 1.3 mg·cm⁻¹. -2 (Based on S8I2).

[0129] The performance of the all-solid-state lithium-sulfur battery prepared in this embodiment was tested: the battery was placed in an oven at 25°C, and a constant current charge-discharge test was performed on a NEWARE battery testing system. The test results are as follows. Figure 12 and Figure 13 As shown, the battery can still deliver 786.3 mAh·g at a charge / discharge rate of 2C. -1 S / I The battery exhibits high specific capacity. Furthermore, it demonstrates extremely high long-cycle stability, retaining 75.8% of its capacity after 9000 cycles. This indicates that even with an increased mass ratio of active material, the S8I2 composite cathode maintains high specific capacity and extremely long cycle life at a high 2C rate.

[0130] Example 6 The difference between the preparation method of the first composite cathode material provided in this embodiment and that in Example 2 is that the mass ratio of the sulfur-iodine complex with the general formula S8I2 to Ketjen black is replaced with 80:20.

[0131] Furthermore, using the first composite cathode material prepared in this embodiment, the second composite cathode material is prepared basically according to the preparation method of the second composite cathode material in Example 2, the difference being that: the S8I2 / KB composite material and the sulfide solid electrolyte Li... 5.5 PS 4.5 Cl 1.5 The mass ratio of the conductive agent Super P is replaced with 7.5:2.1:0.4, that is, the mass fraction of the sulfide solid electrolyte is 21% and the mass fraction of the conductive agent is 4%.

[0132] Using the second composite cathode material obtained in this embodiment, an all-solid-state lithium-sulfur battery was prepared basically according to the preparation method of the all-solid-state battery in Example 2, the difference being: Li 5.5 PS 4.5 Cl 1.5 Replace with an equal mass of 3Li₂S⁻⁴⁵LiI⁻⁂⁵B₂S₃⁻⁰.⁵P₂S₅, and adjust the S₈I₂ loading to 3.4 mg·cm⁻¹. -2 (Based on S8I2).

[0133] The performance of the all-solid-state lithium-sulfur battery prepared in this embodiment was tested: the battery was placed in an oven at 25°C, and a constant current charge-discharge test was performed on a NEWARE battery testing system. The test results are as follows. Figure 14 and Figure 15 As shown, the battery operates at 0.16 mA·cm -2 At a current density of 900.3 mAh·g, it exhibits performance. -1 S / I High specific capacity; it can still achieve 728.0 mAh·g at a charge / discharge rate of 0.2C. -1 S / I It has a high specific capacity and extremely high cycle stability; after 200 cycles, it still retains 722.4 mAh·g. -1 S / I The high specific capacity indicates that even with an extremely high proportion of active material, the S8I2 composite cathode still exhibits a high specific capacity and extremely high long-cycle stability.

[0134] Example 7 The positive electrode active material provided in this embodiment for all-solid-state batteries is a sulfur-iodine composite with the general formula S9I, i.e., x=1. Its preparation method is as follows: weigh elemental sulfur and elemental iodine according to the stoichiometric ratio of S9I, mix and grind them, place them in a sealed glass tube, heat to 80°C and keep warm for 10 hours, then cool naturally to room temperature, take them out and grind them into powder to obtain the sulfur-iodine composite with the general formula S9I.

[0135] Furthermore, using the sulfur-iodine composite with the general formula S9I obtained in this embodiment, a first composite cathode material, namely the S9I / KB composite material, is prepared according to the preparation method of the first composite cathode material in Example 2. Then, the second composite cathode material is prepared using the S9I / KB composite material according to the preparation method of the second composite cathode material in Example 2.

[0136] Then, using the second composite cathode material obtained in this embodiment, an all-solid-state lithium-sulfur battery was prepared according to the preparation method of the all-solid-state battery in Example 2.

[0137] The performance of the all-solid-state lithium-sulfur battery prepared in this embodiment was tested: the battery was placed in an oven at 25°C and constant current charge-discharge tests were performed on a NEWARE battery testing system. Specific capacity and rate were calculated based on the S9I mass. At a charge rate of 10C and a discharge rate of 2C, the specific capacity of the battery was 761.2 mAh·g. -1 S9I .

[0138] Example 8 The positive electrode active material for all-solid-state batteries provided in this embodiment is of the general formula S. 8.57I 1.43 The sulfur-iodine complex, i.e., x=1.43, is prepared by following the method described in S... 8.57 I 1.43 Elemental sulfur and elemental iodine were weighed in stoichiometric proportions, mixed and ground, placed in a sealed glass tube, heated to 80°C and held at that temperature for 10 hours, then naturally cooled to room temperature, removed and ground into powder to obtain the product with the general formula S. 8.57 I 1.43 The sulfur-iodine complex.

[0139] Furthermore, the general formula obtained using this embodiment is S 8.57 I 1.43 The sulfur-iodine complex was used to prepare the first composite cathode material, namely S, according to the preparation method of the first composite cathode material in Example 2. 8.57 I 1.43 / KB composite material, then using this S 8.57 I 1.43 The second composite cathode material was prepared according to the preparation method of the second composite cathode material in Example 2.

[0140] Then, using the second composite cathode material obtained in this embodiment, an all-solid-state lithium-sulfur battery was prepared according to the preparation method of the all-solid-state battery in Example 2.

[0141] The performance of the all-solid-state lithium-sulfur battery prepared in this embodiment was tested: the battery was placed in an oven at 25°C and constant current charge-discharge tests were performed on a NEWARE battery testing system. Specific capacity and rate capability were measured according to S... 8.57 I 1.43 The mass was calculated. At a charge rate of 10C and a discharge rate of 2C, the battery's specific capacity is 813.5 mAh·g. -1 S8.57I1.43 .

[0142] Example 9 The positive electrode active material provided in this embodiment for all-solid-state batteries is a sulfur-iodine composite with the general formula S6I4, i.e., x=4. The preparation method is as follows: elemental sulfur and elemental iodine are weighed according to the stoichiometric ratio of S6I4, mixed and ground, placed in a sealed glass tube, heated to 80°C and kept at that temperature for 10 hours, then naturally cooled to room temperature, taken out and ground into powder to obtain the sulfur-iodine composite with the general formula S6I4.

[0143] Furthermore, using the sulfur-iodine composite with the general formula S6I4 obtained in this embodiment, a first composite cathode material, namely the S6I4 / KB composite material, is prepared according to the preparation method of the first composite cathode material in Example 2. Then, the second composite cathode material is prepared using the S6I4 / KB composite material according to the preparation method of the second composite cathode material in Example 2.

[0144] Then, using the second composite cathode material obtained in this embodiment, an all-solid-state lithium-sulfur battery was prepared according to the preparation method of the all-solid-state battery in Example 2.

[0145] The performance of the all-solid-state lithium-sulfur battery prepared in this embodiment was tested: the battery was placed in an oven at 25°C and constant current charge-discharge tests were performed on a NEWARE battery testing system. Specific capacity and rate were calculated based on the S6I4 mass. At a charge rate of 10C and a discharge rate of 2C, the battery's specific capacity was 601.4 mAh·g. -1 S6I4 .

[0146] Example 10 The positive electrode active material for all-solid-state batteries provided in this embodiment is of the general formula S. 9.5 I 0.5 The sulfur-iodine complex, i.e., x=0.5, is prepared by following the method described in section S. 9.5 I 0.5 Elemental sulfur and elemental iodine were weighed in stoichiometric proportions, mixed and ground, placed in a sealed glass tube, heated to 80°C and held at that temperature for 10 hours, then naturally cooled to room temperature, removed and ground into powder to obtain the product with the general formula S. 9.5 I 0.5 The sulfur-iodine complex.

[0147] Furthermore, the general formula obtained using this embodiment is S 9.5 I 0.5 The sulfur-iodine complex was used to prepare the first composite cathode material, namely S, according to the preparation method of the first composite cathode material in Example 2. 9.5 I 0.5 / KB composite material, then using this S 9.5 I 0.5 The second composite cathode material was prepared according to the preparation method of the second composite cathode material in Example 2.

[0148] Then, using the second composite cathode material obtained in this embodiment, an all-solid-state lithium-sulfur battery was prepared according to the preparation method of the all-solid-state battery in Example 2.

[0149] The performance of the all-solid-state lithium-sulfur battery prepared in this embodiment was tested: the battery was placed in an oven at 25°C and constant current charge-discharge tests were performed on a NEWARE battery testing system. Specific capacity and rate capability were measured according to S... 9.5 I 0.5 The mass was calculated. At a charge rate of 10C and a discharge rate of 2C, the battery's specific capacity is 730.0 mAh·g. -1 S9.5I0.5 .

[0150] Example 11 The positive electrode active material for all-solid-state batteries provided in this embodiment is of the general formula S. 9.75 I 0.25 The sulfur-iodine complex, i.e., x=0.25, is prepared by following the method described in section S. 9.75 I 0.25 Elemental sulfur and elemental iodine were weighed in stoichiometric proportions, mixed and ground, placed in a sealed glass tube, heated to 80°C and held at that temperature for 10 hours, then naturally cooled to room temperature, removed and ground into powder to obtain the product with the general formula S. 9.75 I 0.25 The sulfur-iodine complex.

[0151] Furthermore, the general formula obtained using this embodiment is S 9.75 I 0.25 The sulfur-iodine complex was used to prepare the first composite cathode material, namely S, according to the preparation method of the first composite cathode material in Example 2. 9.75 I 0.25 / KB composite material, then using this S 9.75 I 0.25 The second composite cathode material was prepared according to the preparation method of the second composite cathode material in Example 2.

[0152] Then, using the second composite cathode material obtained in this embodiment, an all-solid-state lithium-sulfur battery was prepared according to the preparation method of the all-solid-state battery in Example 2.

[0153] The performance of the all-solid-state lithium-sulfur battery prepared in this embodiment was tested: the battery was placed in an oven at 25°C and constant current charge-discharge tests were performed on a NEWARE battery testing system. Specific capacity and rate capability were measured according to S... 9.75 I 0.25 The mass was calculated. At a charge rate of 10C and a discharge rate of 2C, the battery's specific capacity is 718.9 mAh·g. -1 S9.75I0.25 .

[0154] Comparative Example 1 The preparation method of the first composite cathode material provided in this comparative example includes the following steps: elemental sulfur and porous conductive carbon material Ketjen black (KB, with the same specific surface area as in Example 2) are mixed at a mass ratio of 75:25, placed in a sealed quartz tube, heated to 155°C, kept at that temperature for 12 hours, and cooled to obtain the S / KB composite material, i.e., the first composite cathode material.

[0155] Then, using the S / KB composite material obtained in this comparative example, a second composite cathode material was prepared according to the preparation method of the second composite cathode material in Example 2.

[0156] Using the second composite cathode material prepared in this comparative example, an all-solid-state lithium-sulfur battery was prepared basically according to the preparation method of the all-solid-state battery in Example 2, the difference being that the sulfur loading in the cathode was 1.0 mg·cm³. -2 (in S).

[0157] The all-solid-state lithium-sulfur battery prepared in this comparative example was subjected to performance testing: the battery was placed in an oven at 25°C and constant current charge-discharge tests were performed on a NEWARE battery testing system. Based on the theoretical specific capacity of S, 1C was defined as 1672 mA·g. -1 S The specific capacity and expansion ratio are calculated based on the mass of elemental sulfur (S). The test results are as follows: Figure 16 and Figure 17 As shown, at a charging rate of 10C and a discharging rate of 1C, the specific capacity of the battery drops to 341.0 mAh·g. -1 S At a charging rate of 24C and a discharging rate of 1C, the battery's specific capacity is only 128.2 mAh·g. -1 S .

[0158] Comparative Example 2 The preparation method of the composite cathode material provided in this comparative example includes the following steps: Li₂S and LiI are mixed at a molar ratio of 8:2 and pre-ball-milled at 500 rpm for 10 h. Subsequently, the ball-milled Li₂S-LiI is mixed with Super P at a mass ratio of 3:2 and ball-milled again at 500 rpm for 10 h. Afterwards, the resulting Li₂S-LiI-Super P composite is combined with Li… 5.5 PS 4.5 Cl 1.5 The Li2S-LiI composite cathode material was obtained by mixing the materials at a mass ratio of 1:1 and ball milling them at 500 rpm for 12 hours.

[0159] Then, using the Li2S-LiI composite cathode material prepared in this comparative example, an all-solid-state lithium-sulfur battery was prepared basically according to the preparation method of the all-solid-state battery in Example 2, the difference being that the S / I loading in the cathode was 0.82 mg·cm³. -2 S / I (Based on S8I2).

[0160] The performance of the all-solid-state lithium-sulfur battery prepared in this comparative example was tested: the battery was placed in an oven at 25°C, and constant current charge-discharge tests were performed on a NEWARE battery testing system. The test results are as follows. Figure 18 and Figure 19 As shown, the battery's specific capacity is 458.3 mAh·g under a charging rate of 10C and a discharging rate of 1C.-1 S / I At a charging rate of 20C and a discharging rate of 1C, the battery's specific capacity drops to 315.9 mAh·g. -1 S / I .

[0161] By comparing Example 2 and Comparative Example 1, the S8I2 / KB cathode exhibited significantly higher capacity retention and lower polarization at high rates, indicating that its solid-to-solid sulfur conversion kinetics were significantly superior to the iodine-free S / KB cathode. This demonstrates that while simply using porous carbon to support sulfur can improve the contact between sulfur and conductive carbon, it cannot effectively solve the problem of the solid-to-solid sulfur conversion reaction being limited by a finite multiphase interface in all-solid-state lithium-sulfur batteries. Pre-introducing an iodine redox medium plays a crucial role in improving high-rate charging performance.

[0162] By comparing Example 2 and Comparative Example 2, although Comparative Example 2 underwent multiple ball milling processes during cathode preparation to maintain solid-phase contact between components, its overall fast charging capability was lower than that of the S8I2 / KB composite cathode. This indicates that the technical effect of the present invention stems from the synergistic effect of structure and mechanism. The pre-embedded, uniformly distributed solid-solid redox medium of the present invention can effectively promote the solid-solid sulfur conversion reaction and significantly improve high-rate charging performance.

[0163] Example 4 illustrates that even with extremely high active material loading, the S8I2 composite cathode still exhibits a very large capacity and a high capacity retention rate.

[0164] Example 5 illustrates that in a composite cathode containing 50 wt% S8I2, a highly active material, the all-solid-state battery still exhibits high specific capacity at a high rate of 2C and has extremely high cycle life.

[0165] Examples 3 and 5 illustrate that the battery assembled with the S8I2 composite cathode not only has high rate performance but also long cycle stability.

[0166] Example 6 illustrates that in a composite cathode containing 60 wt% S8I2 with an extremely high proportion of active material and a high active material loading, the all-solid-state battery still exhibits high specific capacity and extremely high cycle stability.

[0167] The electrical performance results of the all-solid-state lithium-sulfur batteries of Examples 2, 7-9 and Comparative Examples 1-2 are shown in Table 1.

[0168] Table 1. Electrical performance results of all-solid-state lithium-sulfur batteries

[0169] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention; therefore, this means that all such substitutions and modifications that fall within the scope of the present invention are included in the appended claims.

Claims

1. A positive electrode active material for all-solid-state batteries, characterized in that, Including the general formula S 10-x -I x A sulfur-iodine complex, wherein 0.1 ≤ x ≤ 5; The sulfur-iodine complex is heterogeneous and contains both an S phase and an I2 phase. The X-ray powder diffraction pattern of the sulfur-iodine complex shows characteristic peaks of the I2 phase at diffraction angles 2θ of 23.9°±0.2° and 24.3°±0.2°.

2. The positive electrode active material for all-solid-state batteries according to claim 1, characterized in that, At least one of the following conditions must be met: (1) The X-ray powder diffraction pattern of the sulfur-iodine complex has the characteristic peaks of the S phase at diffraction angles 2θ of 23.0°±0.2°, 25.8°±0.2° and 27.7°±0.2°; (2) The cryo-electron microscopy image of the sulfur-iodine complex contains lattice fringes with a crystal plane spacing of 0.405 nm ± 0.005 nm; (3) The cryo-electron microscopy image of the sulfur-iodine complex contains lattice fringes with a crystal plane spacing of 0.365 nm ± 0.005 nm; (4) The cryo-electron microscopy image of the sulfur-iodine complex contains the (220) crystal plane of the S phase and the (200) crystal plane of the I2 phase.

3. The positive electrode active material for all-solid-state batteries according to claim 1, characterized in that, 0.5≤x≤4; Preferably, 1.43 ≤ x ≤ 4.

4. A composite cathode material, characterized in that, Includes the positive electrode active material for all-solid-state batteries as described in any one of claims 1 to 3, and porous conductive carbon materials; The porous conductive carbon material is a carbon material with a porous structure and conductivity. At least a portion of the sulfur-iodine complex is located within the porous structure of the porous conductive carbon material, forming an amorphous structure; During the charge-discharge process, the I2 phase in the sulfur-iodine composite material reacts with I... - The reversible redox reaction between the metal sulfides and sulfur in the composite cathode material accelerates the solid-solid conversion through the reversible redox reaction.

5. The composite cathode material according to claim 4, characterized in that, At least one of the following conditions must be met: (1) The mass ratio of the positive electrode active material for the all-solid-state battery to the porous conductive carbon material is 55~95:5~45; (2) The porous conductive carbon material includes at least one of mesoporous carbon, high specific surface area conductive carbon black, and structured porous carbon, wherein the structured porous carbon has a hierarchical pore structure, preferably the structured porous carbon is an aerogel material or a hollow structure material; preferably, the high specific surface area conductive carbon black includes materials with a specific surface area ≥ 50 m². 2 / g of carbon black; (3) The composite cathode material further includes a solid electrolyte; preferably, the solid electrolyte includes at least one of sulfide solid electrolyte, halide solid electrolyte, oxide solid electrolyte and halide oxide solid electrolyte; preferably, the mass fraction of the solid electrolyte is ≤50%; (4) The composite cathode material further includes a conductive agent; preferably, the mass fraction of the conductive agent is ≤25%.

6. A method for preparing the composite cathode material as described in any one of claims 4 to 5, characterized in that, Includes the following steps: (a) The positive electrode active material for all-solid-state batteries is mixed with porous conductive carbon material, or elemental sulfur and elemental iodine are mixed with porous conductive carbon material, and then heated to melt, so that the molten liquid positive electrode active material for all-solid-state batteries or the liquid mixture of elemental sulfur and elemental iodine enters the pore structure of the porous conductive carbon material, and then cooled.

7. The method for preparing the composite cathode material according to claim 6, characterized in that, Following step (a), the method further includes step (b): mixing the cooled material with a solid electrolyte; During the mixing process in step (b), when the solid electrolyte contains a sulfide solid electrolyte, the sulfide solid electrolyte comes into contact with the I2 phase in the cooled material and undergoes an in-situ redox reaction, causing part of the I2 phase to be converted into LiI nanoparticles, forming an I2 / I2 / LiI nanoparticle. - Nanoscale network structure, which acts as I2 / I - A solid-solid redox medium is pre-introduced into the composite cathode material; during charge and discharge, the I2 / I2 in the composite cathode material... - The nano-network structure undergoes reversible redox reactions, chemically mediating solid-solid transformation of metal sulfide / S; Preferably, the average particle size of the LiI nanoparticles is 2~50 nm.

8. The method for preparing the composite cathode material according to claim 6, characterized in that, A conductive agent is also added during the mixing process in step (b).

9. An all-solid-state battery, characterized in that, It includes a positive electrode composite layer, a solid electrolyte layer, and a negative electrode layer; wherein the positive electrode composite layer contains the positive electrode material as described in any one of claims 4 to 5; Preferably, the solid electrolyte layer is made of inorganic solid electrolyte and / or polymer solid electrolyte, wherein the inorganic solid electrolyte includes at least one of sulfide solid electrolyte, halide solid electrolyte, oxide solid electrolyte and oxyhalide solid electrolyte; Preferably, the material of the negative electrode layer includes at least one of lithium and its alloys, sodium and its alloys, metallic potassium, and metallic aluminum.

10. An electrical appliance, characterized in that, Including the all-solid-state battery as described in claim 9.